THE EFFECT OF LEADERSHIP STYLE ON AUDITOR PERFORMANCE WITH TRUST IN SUPERIORS AS INTERVENING VARIABLE - Budiman, Nita Andriyani (The International Journal of Business Review (The Jobs Review), 2018)
This study aims to examine the influence of leadership styles (transformational and traksaksional) on the performance of auditors (in-role performance and extra-role performance) in the Javanese of public accounting firm through trust in superiors as intervening variables. This study uses questionnaires as a method of collecting data provided to 96 respondents spread across 19 public accounting firm all Java. Hypothesis analysis in this research is conducted by using multiple regression analysis. The results obtained in this study include that the style of transformational leadership does not affect on trust in superiors while the leadership style of transactional positive effect on trust in superiors. In addition, trust in superiors negatively affects in-role performance and positively affects extra-role performance.Â Keywords: Transformational Leadership, Transactional Leadership, In-role Performance, Extra-role Performance, and Trust in Superiors.